Enhancement of catalytic activity for selective hydrogen production from formate with homogeneously poly(vinylpyrrolidone)/cationic poly(l-lysine) dispersed platinum nanoparticles. (9th July 2020) - Minami, Y.; Muroga, Y.; Amao, Y.
Abstract : By using Pt nanoparticles dispersed by polyvinylpyrrolidone and cationic biopolymer, poly(l -lysine) (Pt–PVP/PLL), the highly selective H2 production based on formate decomposition was accomplished compared with that of Pt–PVP. Abstract : Selective H2 production from formate with Pt nanoparticles dispersed by polyvinylpyrrolidone and cationic biopolymer, poly(l -lysine) (Pt–PVP/PLL), is attempted. Using Pt–PVP/PLL, the highly selective H2 production based on formate decomposition was accomplished compared with that of Pt–PVP. Moreover, using Pt–PVP/poly(l -glutamic acid), anionic biopolymer, the catalytic activity for selective H2 production based on formate decomposition was equivalent to that of Pt–PVP. This result suggests that the cationic site of PLL-captured formate ion and promoted the contact with the surface of Pt nanoparticles.